Relationship between Doctors' Prescribing Behavior and Pharmaceutical Promotional Tools: A Pakistani Case - Zaigham Ali; Muhammad Luqman Tauheed Rana; Atif Mahmood; Mian Ahmad Hanan; Saleem Noshina; Khawar Naila (Tehran University of Medical Sciences, 2015)
No Abstract